Development of Idiom Mobile Learning Application: Phraseology - Rosli, Nornaleyda; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2022)
Idiom Mobile Learning Application: Phraseology is an android platform application developed for primary schools aged 12 years old to improve their English idioms knowledge. But with the English language having such an extensive vocabulary and complicated grammar, rarely are students exposed to the slang words used by English speakers in everyday conversation. Hence, the Idiom Mobile Learning Application: Phraseology is proposed to provide an alternative way for primary school students to learn English idioms. The application not only provides the meaning of the idioms but also provides a video on how the English idioms can be used in a conversation. The application is developed in the Android platform by using Unity 2020.3 with references to Agile methodology and it can be installed on any Android platform device. The application is finally developed completely and has achieved all the objectives with beta testing indicating positive feedback of 85.02%.